Fluoresen Klorofil Benih: Parameter Baru dalam Penentuan Mutu Benih - Mohamad Rahmad Suhartanto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2003)
It has been shown that chlorophyll content of seeds was negatively correlated with germinability towards the end of maturation. Physiological maturity was achieved when the chlorophyll fluorescence reached a minimum. The presence of chlorophyll in seeds and its relation with the progress of seed maturation has gained renewed interest after the development of Laser Induced Fluorescence (LIF). This equipment is able to measure and analyze chlorophyll fluorescence in the seed instantaneously and non-destructively. The use of LIF makes it possible to perform physiological and biochemical assays after chlorophyll fluorescence measurement in the same seeds. Based on the results from some experiments as well as the literature, the role of chlorophyll in developing seeds is presented. The overall conclusion is that chlorophyll is required during seed development, but undesirable during maturation. We hypothesize that the presence of chlorophyll during seed maturation is undesirable since it is associated with lower quality, particularly lower seed longevity. Chlorophyll may also be a primary source of free radicals. Seed chlorophyll fluorescence was affected by endogenous abscisic acid, gibberellins and phytochrome. Light, temperature and relative humidity may also influence the chlorophyll fluorescence of seeds. Key words: Chlorophyl, Fluorescence, Parameter, Seed testing